The Integration of Swot and Pestel as a Strategic Approach to Building Sustainable Competitiveness for Financing Companies in an Era of Global Uncertainty - Isti Yuli Ismawati; Tiolina Evi Pardede (Green Publisher Indonesia, 2026)
The financing industry is increasingly challenged by global economic uncertainty, digital disruption, tightening environmental, social, and governance (ESG) regulations, and changing consumer preferences, all of which threaten the long-term competitiveness of financing companies. This study aims to analyze the strategic position of a financing company by integrating SWOT and PESTEL analyses and to formulate adaptive strategies that support sustainable competitiveness under dynamic business conditions. A descriptive qualitative case study approach was employed, focusing on PT BRI Multifinance Indonesia. Secondary data were collected from annual reports, sustainability reports, Financial Services Authority (OJK) publications, industry statistics, and relevant academic literature. The data were analyzed through an integrated SWOT–PESTEL framework and further interpreted using the Dynamic Capability perspective consisting of sensing, seizing, and reconfiguring capabilities. The findings reveal that the company possesses significant strengths in digital innovation, strong institutional support, and risk governance. However, declining profitability, asset growth, and dependence on consumptive financing remain key weaknesses. Externally, ESG implementation, digital transformation, and MSME financing present major opportunities, whereas fintech competition, macroeconomic volatility, and regulatory complexity constitute significant threats. The study concludes that integrating SWOT and PESTEL with dynamic capability provides a comprehensive strategic framework for strengthening sustainable competitiveness through digital transformation, green financing, governance enhancement, portfolio diversification, and continuous organizational adaptation in an increasingly uncertain business environment.